2008
DOI: 10.3390/molecules13051207
|View full text |Cite
|
Sign up to set email alerts
|

Structural Patterns of Rhamnogalacturonans Modulating Hsp-27 Expression in Cultured Human Keratinocytes

Abstract: Polysaccharide extracts were obtained from chestnut bran (Castanea sativa), grape marc (Vitis vinifera) and apple marc (Malus spp.) and fractionated by size exclusion chromatography after endopolygalacturonase degradation. Compositional and linkage analyses by GC and GC-MS showed the characteristic rhamnogalacturonan structure with specific arabinan (apple marc) and type II arabinogalactan (chestnut bran, grape marc) side chains. Type II arabinogalactan rhamnogalacturonan from chestnut bran significantly stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…XGAs are generally susceptible to Exo-PGs, but seldom degraded by Endo-PGs, though an Endo-PG has recently been found to accommodate a xylosylated GalA residue of the backbone just following the hydrolysis site (Mort, Zheng, Qiu, Nimtz, & Bell-Eunice, 2008). Some other reported sources of XGAs are tragacanthic acid (of gum tragacanth from Astralgus gummifer, Leguminosae), kidney and red bean cotyledons, Japanese radish, pea hulls, onion bulbs, cotton seeds, potato tubers, chestnut bran, and grape, pear, apple, citrus and yellow passion fruit rinds (Cui, 2005;Gloaguen et al, 2008;Yapo, 2007Yapo, , 2009a. XGAs are usually found in storage tissues of reproductive organs, and therefore may have specialised functions in these tissues (Albersheim et al, 1996), though they have been identified in non-reproductive organs (roots, stems, and leaves) of diverse plants (Pilarska, Czaplicki, & Konieczny, 2007;Xia, Liu, Zhang, & Luo, 2008;Zandleven et al, 2007), thus suggesting a larger array of functionalities.…”
Section: Xylogalacturonansmentioning
confidence: 97%
“…XGAs are generally susceptible to Exo-PGs, but seldom degraded by Endo-PGs, though an Endo-PG has recently been found to accommodate a xylosylated GalA residue of the backbone just following the hydrolysis site (Mort, Zheng, Qiu, Nimtz, & Bell-Eunice, 2008). Some other reported sources of XGAs are tragacanthic acid (of gum tragacanth from Astralgus gummifer, Leguminosae), kidney and red bean cotyledons, Japanese radish, pea hulls, onion bulbs, cotton seeds, potato tubers, chestnut bran, and grape, pear, apple, citrus and yellow passion fruit rinds (Cui, 2005;Gloaguen et al, 2008;Yapo, 2007Yapo, , 2009a. XGAs are usually found in storage tissues of reproductive organs, and therefore may have specialised functions in these tissues (Albersheim et al, 1996), though they have been identified in non-reproductive organs (roots, stems, and leaves) of diverse plants (Pilarska, Czaplicki, & Konieczny, 2007;Xia, Liu, Zhang, & Luo, 2008;Zandleven et al, 2007), thus suggesting a larger array of functionalities.…”
Section: Xylogalacturonansmentioning
confidence: 97%
“…Strongly stimulating effects of plant polysaccharides on human skin cell physiology have been shown for several times in the recent 0378 (Gloaguen et al, 2008;Deters et al, 2005a,b;Brunold et al, 2004). Especially the strong enhancement of cell viability and proliferation rates in human skin fibroblasts and keratinocytes suggest a positive impact of certain carbohydrates on the regeneration after skin lesions.…”
Section: Introductionmentioning
confidence: 94%